1996
DOI: 10.1016/0014-5793(96)00259-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial import of a yeast cytoplasmic tRNALys: possible roles of aminoacylation and modified nucleosides in subcellular partitioning

Abstract: The yeast tRNAcu U is transcribed from a nuclear gene and then unequally redistributed between the cytosol (97-98%) and mitochondria (2-3%). We have optimized the conditions for its specific import into isolated mitochondria. However, only a minor fraction (about 0.5%) of the added tRNA was translocated into the organelles. An in vitro transcript, once aminoacylated, appeared to be a better import substrate than the natural tRNA which carries modified nucleosides. The tRNA is translocated across mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Although these data support some version of the synthetase model for this tRNA, it should be noted that this tRNA is the only imported tRNA in yeast. Furthermore, it does not appear to function in mitochondrial translation: It is not a substrate for the mitochondrial lysyltRNA synthetase; the yeast mitochondrial genome encodes a lysine tRNA that can decode a similar set of lysine codons; and the acylated form of this molecule is stable in isolated yeast mitochondria (Martin et al 1977(Martin et al , 1979Tarassov et al 1995;Entelis et al 1996). Therefore, the conclusions drawn from these data regarding the role of synthetases in tRNA import may not be generalizable to the import of multiple tRNAs for use in mitochondrial translation.…”
Section: The Potential Role Of Aminoacyl Trna Synthetases In Trna Importmentioning
confidence: 97%
“…Although these data support some version of the synthetase model for this tRNA, it should be noted that this tRNA is the only imported tRNA in yeast. Furthermore, it does not appear to function in mitochondrial translation: It is not a substrate for the mitochondrial lysyltRNA synthetase; the yeast mitochondrial genome encodes a lysine tRNA that can decode a similar set of lysine codons; and the acylated form of this molecule is stable in isolated yeast mitochondria (Martin et al 1977(Martin et al , 1979Tarassov et al 1995;Entelis et al 1996). Therefore, the conclusions drawn from these data regarding the role of synthetases in tRNA import may not be generalizable to the import of multiple tRNAs for use in mitochondrial translation.…”
Section: The Potential Role Of Aminoacyl Trna Synthetases In Trna Importmentioning
confidence: 97%
“…The molecular mechanism of discrimination between imported tRK1 and all the other cytosolic tRNAs was still unknown. Using mutagenesis followed by in vitro and in vivo import assays, we have previously found that not only is tRK1 imported into yeast mitochondria, but also several of its mutant versions, mutants of the second cytosolic lysine isoacceptor tRNA, normally nonimported tRNA Lys UÃUU (tRK2), and even a synthetic transcript of the mitochondrially localized tRNA Lys UÃUU (tRK3) (Entelis et al 1996(Entelis et al , 1998Kolesnikova et al 2002). Systematic analysis of the sequences of imported versions permitted us to discern the determinants (the first base pair G1-C72 and U73 in the acceptor stem and C34 in the anticodon) and an anti-determinant (modified U34) that controls mitochondrial import specificity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The import assay was carried out at 30°C for 20 min, which corresponds to the logarithmic phase of RNA uptake (42). After treatment with a mixture of nucleases (20 units/ml micrococcal nuclease, 50 g/ml RNase A, and 25 units/ml phosphodiesterase), mitoplasts were generated by treatment with digitonin, at 100 g/1 mg of mitoprotein.…”
Section: Methodsmentioning
confidence: 99%
“…For Northern hybridization (23,42), the following 5Ј end-32 P-labeled probes were used: human U3 snRNA, CGCTACCTCTCTTCCTCGTG-GTTTTCGGTGCTCTACA; human cytoplasmic tRNA Met , TGGTAGCA-GAGGATGGTTTCG; human mitochondrial tRNA Cys , AAGCCCCG-GCAGGTTTGAAG; human 5 S rRNA, CCCGACGTTGCTTAACTTC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation